1987
DOI: 10.1038/icb.1987.36
|View full text |Cite
|
Sign up to set email alerts
|

In vivo H‐2K and H‐2D antigen expression In two allogeneic mouse tumours of low immunogenicity

Abstract: Summary The B16 melanoma of C57BL/6 mice immunizes very poorly, even against its own major histocompatibility complex (MHC) antigens. B16 cells expressed both H‐2K and H‐2D antigens in vitro as judged by binding of monoclonal antibodies to these antigens in indirect immunofluorescence staining. The in vivo MHC antigen expression of B16 was examined and compared with that of a second C57BL/6 tumour, the Lewis lung carcinoma (3LL). whose defective immunogenicity has been attributed to a selective deficiency‐ in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

1987
1987
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…MHC-I expression acts as dominant tumour antigen in our model as evidenced by the following observations: (1) when MHC-I expression was up-regulated on B16 melanoma cells by pre-incubation with IFN-γ, the adaptive immune response was stronger and associated with alloreactive antibody production and the inhibition of tumour progression (Figure 2); (2) injection of EL-4 lymphoma (H-2K b ) and MC38 colon cancer cells (H-2K b ) which express normal levels of MHC-I antigens provoked strong alloreactive immune response and were rejected by the allogenic hosts (Figure 2). These results are in line with previous studies demonstrating that low MHC-I antigen expression is associated with tumour growth in allogenic mice [14,15,19,20]. Recent clinical trials in pre-treated small-cell lung cancer (SCLC) patients demonstrated that checkpoint blockade therapies resulted in response rates in only 10% and 25% of patients, which was lower compared to non-small-cell lung cancer (NSCLC) [10,11,12,21].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…MHC-I expression acts as dominant tumour antigen in our model as evidenced by the following observations: (1) when MHC-I expression was up-regulated on B16 melanoma cells by pre-incubation with IFN-γ, the adaptive immune response was stronger and associated with alloreactive antibody production and the inhibition of tumour progression (Figure 2); (2) injection of EL-4 lymphoma (H-2K b ) and MC38 colon cancer cells (H-2K b ) which express normal levels of MHC-I antigens provoked strong alloreactive immune response and were rejected by the allogenic hosts (Figure 2). These results are in line with previous studies demonstrating that low MHC-I antigen expression is associated with tumour growth in allogenic mice [14,15,19,20]. Recent clinical trials in pre-treated small-cell lung cancer (SCLC) patients demonstrated that checkpoint blockade therapies resulted in response rates in only 10% and 25% of patients, which was lower compared to non-small-cell lung cancer (NSCLC) [10,11,12,21].…”
Section: Discussionsupporting
confidence: 93%
“…B16 melanoma injection in allogeneic Balb/c mice, pulmonary metastases were observed from day 7 onwards resulting in 100% animal death. We demonstrated that tumour progression was driven by low expression of MHC-I resulting in insufficient anti-cancer adaptive immune responses [15,16,17,18,19,20], as evidenced by a delayed/decreased alloreactive antibody response. MHC-I expression acts as dominant tumour antigen in our model as evidenced by the following observations: (1) when MHC-I expression was up-regulated on B16 melanoma cells by pre-incubation with IFN-γ, the adaptive immune response was stronger and associated with alloreactive antibody production and the inhibition of tumour progression (Figure 2); (2) injection of EL-4 lymphoma (H-2K b ) and MC38 colon cancer cells (H-2K b ) which express normal levels of MHC-I antigens provoked strong alloreactive immune response and were rejected by the allogenic hosts (Figure 2).…”
Section: Discussionmentioning
confidence: 99%
“…Eisenbaeh and coworkers (23) attributed the failure of allogeneic mice to reject Lewis lung carcinoma to a selective deficiency in the expression of H-2K'' antigen. However, a phenomenon of this type is not responsible for the failure of BALB/c mice reject B16 melanoma, since studies with H-2 recombinant mice have shown that B16 cells can be lysed by cytotoxic cells directed against either H-2K'' or H-2D'' antigens, although both of these antigens were expressed at low levels by B16 cells (31). Festenstein and coworkers (32; 33) have studied MHC Class 1 antigen expression in Gross virus-associated AKR leukaemias and leukaemic cell lines.…”
Section: Why Are Some Tumours Poorly Immunogenic?mentioning
confidence: 99%
“…26]. While the B16 melanoma is of low immunogenicity [27], the macrophages could be induced/activated by other tumor-related stimuli.…”
Section: Discussionmentioning
confidence: 99%